A Review Of The Potential Of Calliandra As A Biomass Power Plant (Journal of Renewable Energy and Mechanics, 2025)
Massively the use of fossil energy makes the earth poisoned by pollution, and the environment is damaged due to the resulting waste. The existence of renewable energy such as biomass can be an existing solution. One example is the calliandra plant which can be useful in many ways. This paper uses the literature review method to show that Calliandra is not only used as livestock feed but could also be used as co-firing fuel as an electric source. Producing a heat of 4,200 kcal/kg so that the ideal calliandra for firewood or charcoal. Calliandra can be used as the co-firing material in the form of biochar with a pyrolysis process.